Immune Checkpoint Inhibitors in Endometrial Cancer: The New Paradigm of Treatment for Advanced and Recurrent Disease - Marta Nerone; Maria Del Grande; Ilaria Colombo (healthbook TIMES. Oncology Hematology)
Endometrial cancer is one of the most prevalent malignancies in women and the prognosis of metastatic and recurrent disease is dismal, with limited treatment options. Molecular classification based on data from the Cancer Genome Atlas (TCGA) project has markedly improved our understanding of the biology of endometrial cancer and accelerated the development of immunotherapy for different disease subtypes. The introduction of immune checkpoint inhibitors (ICIs) has led to major progress in the management of advanced endometrial cancer, especially in biomarker-select populations. Multiple clinical trials have assessed the efficacy and safety of immunotherapy alone or in combination with targeted therapy or chemotherapy in advanced and recurrent endometrial cancer. In this review, we summarize data from recent clinical studies on immunotherapeutic alternatives for advanced and refractory endometrial cancer, with a focus on ICI-based regimens.